Penanaman Karakter Percaya Diri Melalui Kegiatan Ekstrakurikuler Seni Tari Siswa Menengah Pertama Kelas VII di SMP Negeri 46 Palembang - Pebriyanti, Alda; Wardiah, Dessy; Firmansyah, Feri (Institut Teknologi Pendidikan Indonesia, 2022)
The background of this research is the growth of self-confidence character is very important and needs special attention because it is one of the preventive efforts to overcome the character crisis that occurred in Indonesia, so it is hoped that the activities that have been carried out must continue to be strengthened and further developed in order to produce the seeds of the nation's generation who have a strong self-confident character. The problem for this researcher is how is the process of instilling a confident character through dance extracurricular activities at SMP Negeri 46 Palembang, the background of this research is therefore the purpose of this study to find out and describe the process of instilling a confident character through dance extracurricular activities in junior high schools. Negeri 46 Palembang. Data collection techniques used in this study are observation, interviews, and documentation. The data analysis technique used is data reduction, data presentation, and conclusions based on research results instilling a confident character through dance extracurricular activities at SMP Negeri 46 Palembang which uses the drill method in itslearning process. The results of this study are included in the good category because they can find out the various characteristics of students when doing dance movements. This can be seen from the observations of students who achieve well and students who are able to learn traditional dance movements very well. This study takes one character in traditional dance extracurriculars, namely the confident character and does not take all characters.